A Mini Review on Carbon Quantum Dots: Preparation, Properties, and Electrocatalytic Application - Wang, Xiao; Feng, Yongqiang; Dong, Peipei; Huang, Jianfeng (Frontiers in Chemistry, 2019)
Luminescent carbon quantum dots (CQDs) are a new form of nanocarbon materials that have gained widespread attention in recent years, especially in chemical sensing, biosensing, bioimaging, nanomedicine, photocatalysis and electrocatalysis. CQDs can be prepared simply and inexpensively by multiple techniques, such as the arc-discharge method, microwave pyrolysis, hydrothermal method and electrochemical synthesis. CQDs show excellent physical and chemical properties like high crystallization, good dispersibility, photoluminescence properties. In particular, the small size, superconductivity and rapid electron transfer of CQDs endow the CQDs-based composite with improved electrical conductivity and catalytic activity. Besides, CQDs have abundant functional groups on the surface which could facilitate the preparation of multi-component electrical active catalysts. The interactions inside these multi-component catalysts may further enhance the catalytic performance by promoting charge transfer and intermolecular electron transfer which plays an important role in electrochemistry. Most recent researches on CQDs have focused on their fluorescence characteristics and photocatalytic properties. This review will summarize the primary advances of CQDs in the synthetic methods, excellent physical and electronic properties, and application in electrocatalysis, including oxygen reduction reaction (ORR), oxygen evolution reaction (OER), hydrogen evolution reduction (HER) and CO2 reduction reaction (CO2RR).